Location determination by processing signal strength of Wi-Fi routers in the indoor environment with linear discriminant classifier - Altay, Osman; Ulas, Mustafa (Institute of Electrical and Electronics Engineers Inc., 2018)
Location determination in the indoor areas as well as in open areas is important for many applications. But location determination in the indoor areas is a very difficult process compared to open areas. The Global Positioning System (GPS) signals used for position detection is not effective in the indoor areas. Wi-Fi signals are a widely used method for localization detection in the indoor area. In the indoor areas, localization can be used for many different purposes, such as intelligent home systems, locations of people, locations of products in the depot. In this study, it was tried to determine localization for with the classification method for 4 different areas by using Wi-Fi signal values obtained from different routers for indoor location determination. Linear discriminant analysis (LDA) classification was used for classification. In the test using 10k fold cross-validation, 97.2% accuracy value was calculated. © 2018 IEEE.
6th International Symposium on Digital Forensic and Security, ISDFS 2018 -- 22 March 2018 through 25 March 2018 -- Antalya -- 136277
Keywords: classification; linear discriminant analysis; location determination; Wi-Fi signal strength